Influence of surface structure and morphology of PEDOT: PSS on its optical and electrophysical characteristics - А.К. Аймуханов; К.С. Рожкова; А.К. Зейниденов; Т.Е. Сейсембекова (Қарағанды университетінің хабаршысы. Физика сериясы)
This paper presents the results of a study of the effect of modification of the structure of the PEDOT: PSS polymer with hole conductivity on the optical and electrophysical properties of an organic solar cell. It was found that the modification of a polymer film with ethyl and isopropyl alcohols leads to a change in the morphology and roughness of the film surface. It has been determined that annealing of films in alcohol vapor promotes the formation of more uniform films. It is shown that upon modification of the PEDOT: PSS film in alcohol vapor the absorption spectrum shifts the absorption maximum of PEDOT to the short-wavelength region of the spectrum, the absorption of the aromatic PSS fragment decrease. X-ray phase analysis showed that after surface modification with alcohol vapor, the PEDOT and PSS chains change their structure. It is shown that the structural features of the surface morphology of PEDOT: PSS affect the electrophysical parameters of the films, such as the effective extraction rate and the effective time of flight of charge carriers. It was found that the modification of the surface of the PEDOT: PSS film leads to an improvement in the electrical transport properties of the films.